The Influence of Product Quality, Price Perception, and Brand Image on Purchase Decisions for Yakult Drinks in East Jakarta - Sendy Priskilla; Resti Hardini; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This research aims to analyze the influence of product quality, price perception and brand image on purchasing decisions for Yakult drinks in East Jakarta. This research data uses primary data in the form of a questionnaire to 100 respondents who have consumed Yakult drinks in East Jakarta. The data analysis technique uses inferential analysis with multiple linear regression and uses the Statistical Product and Service Solution (SPSS) version 26.0 program. The results of multiple linear regression analysis show that the variables Product Quality (X1), Price Perception (X2), and Brand Image (X3) have a positive and significant effect on the Purchase Decision for Yakult drinks in East Jakarta. The existence of a positive and significant influence between product quality, price perception and brand image shows that the higher the level of product quality, price perception and brand image, the higher the decision to purchase Yakult drinks in East Jakarta.